leA New Methodology for Calculating Electromagnetic Transients in Transmission Lines - Colqui, Jaimis S. L. [UNESP]; Araujo, Anderson R. J. de [UNESP]; Kurokawa, Sergio [UNESP]; Tsuzuki, MDG; Junqueira, F. (Ieee, 2018)
This paper shows a simple and efficient methodology using recursive convolutions and Vector Fitting to simulate electromagnetic transients of a single-phase transmission line during a switching procedure directly in the time domain. To validate the proposed methodology, it was tested in a singlephase transmission line considering diverse excitation voltage source and different conditions in its receiving end. The results are compared by the Universal Line Model, which is developed in frequency domain and it uses the Numerical Inverse Laplace Transform (NLT) to obtain the time domain responses. The results showed that proposed method is accurate besides its friendly implementation and can be employed in transient analysis.
Keywords: Electromagnetic transients; transmission lines; frequency domain; vector fitting; recursive convolution